Survey of adaptive physical education learning implementation in the SLB A in Surakarta in the academic year of 2019/2020 - Afinda Devibrillianita Sandhy; Djoko Nugroho; Tri Winarti Rahayu (PJKR FKOR UNS, 2020)
The learning and teaching process of adaptive physical education subject in SLB A or special school A in Surakarta (SLB Negeri Surakarta and SLB A YKAB Surakarta) have faced several obstacles such as the education background of the physical education teachers which are special education background not the physical education background, teachers are still unable to pay attention to the students entirely and to the aspects included in learning implementation, the lack of learning facilities and infrastructure, adaptive physical education learning that generalizes various types of disabilities, and the inactivity of students in participating in the learning process. Therefore, this study aims to discover the implementation of adaptive physical education learning process in SLB A in Surakarta. This study used quantitative method. The approach used in this study was descriptive approach and the research method used was survey method with data collecting technique of observation, questionnaire, and document study. The collecting technique used by the author was by including all of the study’s subjects as the respondents. The collected data was analyzed and tested its validity using triangulation data and triangulation method. The result of this study shows that the Implementation of Adaptive Physical Education Learning in SLB A in Surakarta in the Academic Year of 2019/2020 is lacking based on its influenced factors. Therefore, it is necessary to review and improve the policies in the adaptive physical education learning for visual impaired students.